2018
DOI: 10.1259/bjr.20170683
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of image quality on acquisition protocol and image processing in chest tomosynthesis—a visual grading study based on clinical data

Abstract: The study indicates that the protocol with 6.3 s acquisition time yields slightly better image quality than the vender-recommended protocol with acquisition time 12 s for several anatomical structures. Furthermore, the standard gradation processing  (the vendor-recommended post-processing for DTS), yields to some extent advantage over the gradation processing/multiobjective frequency processing/flexible noise control processing in terms of image quality for all classes of criteria. Advances in knowledge: The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…5 The second option is prefer-able as it allows us to maintain a higher FE level and to better assess bone structures. 21 In agreement with our results, previous studies have shown that FNC is an effective approach to reduce noise in human radiography. 4,15 FNC is a multiresolution filter, which in contrast to a simple average filter (i.e., linear low-pass filters) does not blur the whole image but is able to preserve edges and anatomical structures.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…5 The second option is prefer-able as it allows us to maintain a higher FE level and to better assess bone structures. 21 In agreement with our results, previous studies have shown that FNC is an effective approach to reduce noise in human radiography. 4,15 FNC is a multiresolution filter, which in contrast to a simple average filter (i.e., linear low-pass filters) does not blur the whole image but is able to preserve edges and anatomical structures.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, if high quantum noise is present, as in low‐dose imaging, enhancing the contrast with FE leads to an accentuation of the already present noise, and the FE process thus may be deleterious 5 . The second option is preferable as it allows us to maintain a higher FE level and to better assess bone structures 21 . In agreement with our results, previous studies have shown that FNC is an effective approach to reduce noise in human radiography 4,15 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The ViewDEX software can be downloaded free of charge from www.vgregion.se/sas/viewdex , and in the end of October 2020 ViewDEX had been downloaded from over 40 countries and had received over 230 citations in scientific publications. ViewDEX has for example been used for studies in conventional projection radiography ( 6 ) , tomosynthesis ( 7 ) , computed tomography (CT) ( 8 ) , mammography ( 9 ) , magnetic resonance imaging (MRI) ( 10 ) , nuclear medicine imaging ( 11 ) , interventional imaging ( 12 ) and ultrasound ( 13 ) .…”
Section: Introductionmentioning
confidence: 99%